KONSTELASI INSTITUSI PEMERINTAH DAN LEMBAGA SWADAYA MASYARAKAT DALAM PROGRAM PIDRA - Iqbal, Muhammad (Universitas Muhammdaiyah Surakarta, 2008)
Apart from governmentâs role, it is necessary to implement the development program by participatory contribution of stakeholders which is among others from non-governmental organization (NGO). One of development programs implemented from national level up to village level through constellation of government institution and NGO is PIDRA. At village level, both constellations were represented by field technical assistant of government institution and facilitator of NGO to which it employed synergic activities with community. The implementation of PIDRA Program brought positive impact on community empowerment in terms of capacity building and institutional development. Hence, experimental experience of PIDRA Program is strategically implemented in other program sites based on participatory collaborative management.